(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Background: AI: language=EN Artificial Intelligence (AI) is taking center stage in public debate but its mediatized representations have a clear ideological bent. The media characterises AI with stories of fear, power and techno-hype, perceptions that in return shape, and in a way "define," AI policies. Objectives: This research attempts to critically examine how AI is discursively framed in English-language media following Fairclough’s Critical Discourse Analysis (CDA) and Foucault’s power/knowledge alongside exploring ideological implications in media language. Methods: Fifty-one news articles published between November 2022 and March 2023 formed the qualitative corpus that was analyzed. Sources range from the largest English-speaking country, the USA, to the India and New Zealand. In this analysis, lexical choices, metaphors and figures of speech were examined using a CDA approach. Results: The research identifies one dominant triad that structures AI rhetoric: • Power: From humans to machines, the rise of Big Tech narratives. • Fear: Military metaphors, future panic, displacement rhetoric. • Hype: Idealistic framing and promises of exaggerated progress. Such discourses neglect alternate voices, and occlude more complex discussion. Discussion: Media representations are ideological instruments in the service of construction of public consciousness and policy orientation. The results indicate a set of epistemic risks, which affect both misleading or fake news, digital divide and gatekeeping of public speaking on the Web by gauging on the privilege. Conclusion: AI in (English language) media discourse is not neutral—it is a site of power struggle. The paper argues for ethical journalism, AI literacy and a more inclusive public discourse that challenges polarising and sensationalist news stories.